Age-related changes to human stratum corneum lipids detected using time-of-flight secondary ion mass spectrometry following in vivo sampling - Starr, Nichola J.; Johnson, Daniel J.; Wibawa, Judata; Marlow, Ian; Bell, Mike; Barrett, David A.; Scurr, David J. (American Chemical Society, 2016)
This work demonstrates the ability to detect changes in both quantity and spatial distribution of human stratum corneum (SC) lipids from samples collected in vivo. The SC functions as the predominant barrier to the body, protecting against the penetration of xenobiotic substances. Changes to the SC lipid composition have been associated with barrier impairment and consequent skin disorders and it is therefore important to monitor and quantify changes to this structure. This work demonstrates the first reported use of time of flight secondary ion mass spectrometry (ToF-SIMS) to assess physiological changes to human SC as a function of depth. This technique provides exceptional sensitivity and chemical specificity, al-lowing analysis of single tape stripped samples taken from volunteers. Using this methodology we were able to successfully identify chemical differences in human SC resulting from both intrinsic and extrinsic (photo) aging. Samples were collected from women of two age groups (under 27 and post-menopausal) and from two body sites with varying UV exposure (inner forearm and dorsal hand) and differences were identified using multivariate data analysis. The key finding was the signifi-cant aged-related increase and change in spatial distribution of the sterol cholesterol sulfate, a membrane stabilizing lipid. Significant changes in the prevalence of both lignoceric acid (C24:0) and hexacosanoic acid (C26:0) were also observed. This work describes previously unreported age-related chemical changes to human SC, providing an insight into aging mechanisms which may improve the design of both pharmaceutical and cosmetic topical products.